2018
DOI: 10.3390/app8040587
|View full text |Cite
|
Sign up to set email alerts
|

Preparation Techniques of TiO2 Nanofluids and Challenges: A Review

Abstract: Titanium dioxide (TiO 2 ) has been used extensively because of its unique thermal and electric properties. Different techniques have been used for the preparation of TiO 2 nanofluids which include single-step and two-step methods. In the natural world, TiO 2 exists in three different crystalline forms as anatase, brookite, and rutile. Nanoparticles are not used directly in many heat transfer applications, and this provides a major challenge to researchers to advance towards stable nanofluid preparation methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(70 citation statements)
references
References 105 publications
(124 reference statements)
0
70
0
Order By: Relevance
“…As is known from the literature, one of the main difficulties associated with the preparation of stable electro-insulating nanofluids is the fact that nanoparticles are hard-soluble compounds, or insoluble in base liquids [33,61]. It is difficult to obtain a stable dispersion of nanoparticles in electro-insulating liquids.…”
Section: Preparation Of Nanofluids Based On Fullerene C 60mentioning
confidence: 99%
See 1 more Smart Citation
“…As is known from the literature, one of the main difficulties associated with the preparation of stable electro-insulating nanofluids is the fact that nanoparticles are hard-soluble compounds, or insoluble in base liquids [33,61]. It is difficult to obtain a stable dispersion of nanoparticles in electro-insulating liquids.…”
Section: Preparation Of Nanofluids Based On Fullerene C 60mentioning
confidence: 99%
“…Recently, an increasing amount of research related to the search for alternative electro-insulating liquids has focused on the use of nanotechnology [31]. By dispersing nanometric materials (nanoparticles, nanofibers, nanotubes, nonowires, nonorods, nonosheets) in base fluids, a new class of dielectric liquids called nanofluids can be obtained [32,33]. Choi invented this term in 1995 [34].…”
Section: Introductionmentioning
confidence: 99%
“…Galstyan et al illustrated the gas-sensors application of TiO 2 fabricated using physical and chemical methods [13]. Ali et al illustrated the preparation methods of TiO 2 including one-step and two-step, and focused on the application of TiO 2 nanofluids in heat transfer [14].…”
Section: Introductionmentioning
confidence: 99%
“…Numbers of review articles have also been published covering the methods of preparation, the characterization, the modeling and the application areas (e.g. [6][7][8][9]). They concluded that more research is required to simplify the methods of preparation of nanofluids in order to make them cost effective.…”
Section: Introductionmentioning
confidence: 99%